Pakistan Cotton Survey 2013, round 1.1 - International Food Policy Research Institute; Innovative Development Strategies; National Institute of Genomics and Advanced Biotechnology, National Agricultural Research Center; University of Agriculture, Faisalabad (International Food Policy Research Institute, 2016)
The dataset "Pakistan Cotton Survey 2013, Round 1.1" was collected to inform the research study that examines the efficiency of markets for cotton seed in Pakistan with particular emphasis on the market for genetically modified cotton seed embodying insect-resistance traits from the soil bacterium Bacillus thurigiensis (Bt) that have been conferred through genetic modification. The survey was designed by the International Food Policy Research Institute (IFPRI) and implemented by Innovative Development Studies (IDS). It collected data on household, farm and plot characteristics of cotton growers. Data were collected in face-to-face interviews with 728 farmers who were selected in a statistically representative sample of all cotton-growing agroclimatic zones in both Punjab and Sindh Provinces, accounting for more than 99 percent of the cotton cultivated in Pakistan. The first round was implemented between March-May in 2013, soon after participants planted cotton.